Bone marrow stromal cells reverse the microglia type from pro-inflammatory tumour necrosis factor a microglia to anti-inflammatory CD206 microglia of middle cerebral artery occlusion rats through triggering secretion of CX3CL1 - Bai, Xiu-Juan; Hao, Lei; Guo, Yan-E; Shi, Xiao-Bing; Wu, Wei-Ping (Folia Neuropathologica, 2021)
The middle cerebral artery occlusion (MCAO) model has been extensively applied to study ischaemic stroke. This study attempted to clarify effect of bone marrow stromal cells (BMSCs) on infarct injury of MCAO rats. BMSCs were isolated and identified by staining CD29/CD44 and CD31/CD45. CX3CL1 silencing vector (pLVX-shRNA-CX3CL1) was generated and infected to BMSCs. pLVX-shRNA-CX3CL1 infected BMSCs were transplanted into brain tissue of MCAO rats. Real-time PCR was used to determine CX3CL1 expression. Infarct areas were stained with TTC to evaluate infarct size. Double-staining immunofluorescence was conducted to determine anti-inflammatory type CD206 and pro-inflammatory type tumour necrosis factor a (TNF-a) microglia. Isolated BMSCs were positively presented for CD29/CD44, and negatively for CD31/CD45. CX3CL1 was significantly lower in the BMSC + pLVX-shRNA2-CX3-CL1 group compared to the BMSCs + pLVX group (p < 0.05). According to TTC and neurological scores, MCAO rats were successfully generated. BMSCs transplantation significantly increased CD206 microglia and decreased TNF-a microglia. However, shRNA-CX3CL1-infected BMSCs remarkably reduced CD206 microglia and enhanced TNF-a microglia compared to the MCAO + BMSCs group. In conclusion, BMSCs reverse microglia from pro-inflammatory type TNF-a microglia to anti-inflammatory type CD206 microglia in the infarct region of MCAO rats (3rd to 7th days post BMSC transplantation), through triggering of CX3CL1 secretion. Therefore, the potential effects of CX3CL1 secreted by BMSCs would provide an insight for stem cell-dependent therapeutic strategies in treating ischaemic stroke-associated disorders.